Effects of cognitive remediation therapy versus other interventions on cognitive functioning in schizophrenia inpatients. Issue 3 (16th March 2019) - Linke, Magdalena; Jankowski, Konrad S.; Wichniak, Adam; Jarema, Marek; Wykes, Til
ABSTRACT: Computerised cognitive remediation therapy (CCRT) has been shown to improve cognitive function in individuals with schizophrenia beyond effects of other forms of therapy. However, results vary between studies, and most are aimed at individuals who are living in the community. Very few studies have investigated its efficacy in psychiatric wards in order to assess whether or not this is a suitable site to start the therapy. This study evaluated CCRT efficacy among schizophrenia inpatients who received a broad range of therapeutic interventions in a psychiatric ward. A randomised controlled trial of CCRT versus an active control in 66 young inpatients with a diagnosis of schizophrenia was conducted. The intervention lasted for 6 weeks and its efficacy was assessed with the composite score of the MATRICS Consensus Cognitive Battery. Both groups improved similarly in cognitive function and psychopathological symptoms. However, the CCRT group improved more than the controls in negative symptoms. This result shows that providing a drill and practice cognitive remediation to inpatients does not produce benefits for cognitive functioning substantially greater than other forms of therapy provided in a ward, but it is more efficient in reduction of negative symptoms. Our results suggest that CRT might be considered as a promising intervention for reducing negative symptoms in schizophrenia individuals.